From a Tokotoko: Pacific Travels with Professor Angelo - Townend, Andrew (Victoria University of Wellington Law Review, 2008)
This article is a tribute to Professor Tony Angelo from the author who served as Professor Angelo’s research assistant from 2002 to 2004, accompanying him on several trips to Tokelau, the Marshall Islands, and Niue. The article provides accounts of their trips together, as well as insights into Professor Angelo’s admirable work ethic and meticulous preparation. The author praises Professor Angelo’s role as a mentor, a bringer of consistency to the law, and the development of law attuned to local circumstances.